1985
DOI: 10.1161/01.hyp.7.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell abnormalities and spontaneous hypertension in the rat. A genetically determined link.

Abstract: The significance of the erythrocyte abnormalities described in rats and humans with spontaneous hypertension is far from clear. This study, in two highly inbred strains of rats, was designed to evaluate whether these abnormalities are primary and thus genetically related to hyper-tension. The Milan hypertensive strain (MHS) and its normotensive control strain (MNS) were used to carry out two types of experiments. In two groups of lethally irradiated (MHS x MNS) F, hybrids, bone marrow from MHS or MNS was trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 22 publications
1
33
0
2
Order By: Relevance
“…An increased platelet membrane microviscosity has been described in spontaneously hypertensive rats and ascribed either to protein (32) or to fatty acid (33) constituents of the membrane. The fatty acid contents of platelet and red cell membranes appear to be genetically determined and associated with either a family history or the development of hypertension in rats and men (34,35). Exactly how these membrane alterations interact with agonist-mediated adrenergic receptor desensitization and whether they may be the source ofthe defect identified in human essential hypertension remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…An increased platelet membrane microviscosity has been described in spontaneously hypertensive rats and ascribed either to protein (32) or to fatty acid (33) constituents of the membrane. The fatty acid contents of platelet and red cell membranes appear to be genetically determined and associated with either a family history or the development of hypertension in rats and men (34,35). Exactly how these membrane alterations interact with agonist-mediated adrenergic receptor desensitization and whether they may be the source ofthe defect identified in human essential hypertension remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Altered activity of the Na -K pump and/or Na -K cotransport system (HTG) (15,16). Genetic analysis based upon F2 hybrids or recombinant inbred strains revealed a significant cosegregation of blood pressure with abnormal Na -K cotransport (13,17) or enhanced Na leak (15,18).…”
Section: Introductionmentioning
confidence: 99%
“…On the assumption that the underlying molecular determinant was ubiquitous, the investigation was extended to other cell types. In erythrocytes, significant differences in Na ϩ -K ϩ co-transport between the two strains were reported that cosegregated with arterial pressure in appropriate genetic crosses (Bianchi et al 1985).…”
Section: Adducinmentioning
confidence: 99%